Periodic attractors of nonautonomous flat-topped tent systems - Silva, Luis (2019)
In this work we will consider a family of nonautonomous dynamical systems x(k)(+1) = f(k)(x(k), lambda), lambda is an element of [-1, 1] (N0), generated by a one-parameter family of flat-topped tent maps g(alpha) (x), i.e., f(k)(x, lambda) = g(lambda k) (x) for all k is an element of N-0. We will reinterpret the concept of attractive periodic orbit in this context, through the existence of some periodic, invariant and attractive nonautonomous sets and establish sufficient conditions over the parameter sequences for the existence of such periodic attractors.